Atypical polypoid adenomyoma follow-up and management: Systematic review of case reports and series and meta-analysis. Issue 26 (26th June 2020) - Biasioli, Anna; Londero, Ambrogio P.; Orsaria, Maria; Scrimin, Federica; Mangino, Francesco Paolo; Bertozzi, Serena; Mariuzzi, Laura; Cagnacci, Angelo
Abstract: Background: Atypical polypoid adenomyoma (APA) is a rare uterine tumor typically found in fertile age and associated with infertility. Among young nullipara women, conservative treatment is proposed despite the high recurrence rate and the association with endometrial cancer. Our aim was to assess the risk of recurrence with different conservative treatments in fertile ages and the prevalence of malignant or pre-malignant associated lesions to better address an adequate patient counselling when treatment modalities are discussed. Methods: This study is a systematic review and meta-analysis of case reports and case series about APA management and follow-up. A literature search was carried from Medline and Scopus for studies published from January 1, 1980 to December 31, 2018. Results: We included 46 observational studies and 296 cases in fertile women. The prevalence of APA relapse was 44% (CI.95 33–57%) and was lower in cases treated with operative hysteroscopy (22%; CI.95 11–39%) than in cases treated with blind curettage and polypectomy (38%; CI.95 15–67%). The prevalence of the concomitant or during the follow-up diagnosis of endometrial carcinoma was 16% (CI.95 9–29%). The risk of cancer development during follow-up was significantly less in cases treated with histeroscopy (10.56% new cumulative diagnosis at 5 years follow up; CI.95 0–23.7%) than blind curettage and polypectomy (35.5% new cumulative diagnosis at 5 years; CI.95 11.65–52.92%; P  < .05). Medical treatment with medroxyprogesterone acetate after surgery does not reduce APA recurrence. Pregnancy was observed in 79% cases in which the desire was expressed. Conclusion: This review suggests that conservative treatment performed by operative hysteroscopy is the optimal choice because it lowers the risk of recurrence, improves the accuracy of concomitant carcinoma or hyperplasia diagnosis, and leaves the possibility of future pregnancies. Abstract : Supplemental Digital Content is available in the text